Manajemen Pengelolaan Dan Strategi Pemasaran Dalam Konsep Ekonomi Islam Pada Mini Market Syariah Di Tanjung Pura - H. Anjur Perkasa Alam, Asmawarna Sinaga, Khairani Sakdiah, Afifah Yasmin, Cici Oktari (CV. Pusdikra Mitra Jaya, 2022)
Management is a plan where everything is done steadily to give birth to beliefs that have an impact on doing things according to the rules and having benefits. The planning function includes strategy, and strategy is an integral part of a business or company. Likewise, the success of a product being accepted by the target market is not only determined by the low price or quality offered, but is also determined by the marketing strategy undertaken. Consumers who come to the supermarket take the goods they want to buy themselves. This is what distinguishes supermarkets from traditional stalls. In traditional stalls, consumers are served by the shop owner if they want to take the goods they want to buy. This is what motivates consumers to shop at mini markets instead of stalls or other traditional shops. The identification in this study are: 1. There is motivation for consumers to shop at mini markets rather than to warungs or other traditional stores. 2. One of the important management concepts to be applied for modern retail companies (minimarkets) is the handling and procurement of goods. 3. Mini market in Tanjung Pura, there is one sharia-based mini market which is quite familiar to the public, namely sharia mini market. Management is the utilization of physical and human resources through coordinated efforts and is completed by carrying out the functions of planning, organizing, compiling, directing and supervising. In this opinion, it is well realized how important the role of the resources owned by the organization, both human resources and material resources. Because the use of these two resources by managers in an organization effectively and efficiently will optimize the achievement of organizational goals. Utilization of organizational resources starting from proper planning, solid organization, proper and professional staffing, well-controlled direction and supervision will ensure the functioning of the managerial process. The research method used is the instrument used in this study is a human instrument, because the data collected is through the main instrument, namely the researcher himself. The data collection needed in this study was carried out using techniques adapted to the situation and conditions of the research field. With a good management concentration and based on Islamic Economics, it can make the management of sharia mini markets better and can be a reference for other mini markets. One of the important management concepts to be applied for modern retail companies (minimarkets) is the handling and procurement of goods. The term most often used by retail entrepreneurs for the handling and procurement of goods in their outlets is called merchandising. Meanwhile, retail players carry out the functions of purchasing, keeping inventory, promoting, selling, sending and paying to agents or distributors. Retail does not manufacture goods and does not sell to other retailers. This can be a special attraction if the current business can keep up with the times and provide satisfied value to consumers. The strategy carried out by Islamic retail business owners in facing the fast economy is only to do the right product, right quantity, and right price strategy. From the strategies carried out, it can be understood that the existing strategies have increased in the efforts carried out by Islamic retail business owners. While the inhibiting factors include: weak decision-making abilities and weak promotions on social media because knowledge for Islamic retailers in information and communication technology (internet) is still lacking.